A MAJESTOSA TRILHA AXIOLÓGICA DE PODER E DEMOCRACIA NAS OBRAS DE RUTH ROCHA - MACHADO, THAIANE MILEIDI KLEMS (2024)
As the theoretical assumptions of the Bakhtin Circle point out, utterances concretize social relations. Thus, whenever an utterance is addressed to the other, it is accompanied by an evaluative tone, emotions, feelings and social, historical and cultural values. From this perspective, this research seeks to understand the axiological constitution of the statements of Ruth Rocha's series of kings. To this purpose, the research is supported by the theoretical contribution of the Bakhtin Circle (BAKHTIN, 2003, 2016, 2017; VOLÓCHINOV 2019, 2021 and MEDVIÉDEV, 2019) and other contemporary Brazilian researchers, whose field nuances the studies of Dialogic Discourse Analysis (ADD). Methodologically, qualitative-interpretative research is adopted, anchored in the sociological method of the theory of Dialogism. As the corpus of the work, four short stories were selected, belonging to Ruth Rocha's quadrilogy of kings, composed of O reizinho mandão (2013 [1978]), O rei que não sabia de nada (2012 [1980]), O que os olhos não veem (2012 [1981]) and Sapo vira-rei-vira sapo ou A volta do reizinho mandão (2012 [1982]). From this study, we were able to show that children's stories are voices to refract and reflect ideologies and values determined by the chronotope of the military dictatorship. It was found that the axiological elements that emerge in the reading of the tales constitute a position of criticism of the dictatorial regime and the aggressive and authoritarian positions with the opponents of the regime and the population in general. It is understood that linguistic and extraverbal resources contribute to an evaluative position of repudiation of authoritarianism and censorship, at the same time, placing the child as a questioner, reflexive and critical in the face of current social demands. Thus, the reading of the tales enables the reader to understand, assimilate and re-signify the values circulating in society, in a new chronotope, contributing to the expansion of the child's socio-ideological awareness, to position himself through language and affirm himself as a socially and historically constructed subject.